Tinjauan Aplikasi Teknologi Edible Coating Polimer Alami: Kontrol Transpirasi dan Mutu Produk Pascapanen - Viantika Gea, Anesti (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2026)
Edible Coating (EC) is an advanced postharvest technology that utilizes natural biopolymers to prolong the shelf life of horticultural products by forming a safe-to-consume, semi-permeable barrier layer. This systematic review provides an in-depth analysis of the roles of natural polymers (carbohydrates, lipids, and proteins) and their active formulations (incorporating antimicrobial/antioxidant extracts) in controlling the two main mechanisms of postharvest decay: transpiration (weight loss) and respiration (softening).The synthesis of the literature indicates that lipid polymers, particularly beeswax, are the superior EC component for suppressing the rate of transpiration in commodities such as tomatoes. A formulation containing 25 g of beeswax was proven effective in maintaining the lowest weight loss percentage during 30 days of storage. Conversely, polysaccharide polymers (e.g., cassava starch, jackfruit seed starch) are highly effective at limiting gas exchange, suppressing respiration rates, and preserving firmness. Specifically, an EC using 1.1% jackfruit seed starch on guava successfully maintained quality for up to 10 days. Furthermore, the development of active ECs such as those enhanced with 7% red ginger extract in corn starch, or lemongrass and sesame oil in beeswax emulsions synergistically boosts antimicrobial and antioxidant functions. This dual action is crucial for preserving vital nutrients like Vitamin C and pigments. The EC technology is thus confirmed as a promising coating alternative, strongly supported by the significant potential for utilizing polymers derived from agro-industrial waste.